SOSIALISASI PENINGKATAN KAPASITAS TENAGA MEDIS DALAM PEMULASARAAN JENAZAH COVID-19 - Taufik Hidayat; Rika Susanti; Afriwardi Afriwardi; Citra Manela; Noverika Windasari (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
Transmission of the coronavirus that causes COVID-19 from corpses to people around, namely mortuary officers and the families of the bodies, can occur through direct contact with body fluids, objects around the body that are contaminated with the coronavirus, and aerosols formed when the body is moved or turned over. The curing of the COVID-19 corpse requires special treatment so that the custodian of the corpse avoids the transmission of this coronavirus. The purpose of this activity is to increase the knowledge and awareness of medical and mortuary staff about the importance of organizing COVID-19 bodies by taking into account the standards that the WHO has issued, professional organizations while still paying attention to the ethical, religious, and customs aspects of the local community. This capacity-building method is in the form of an online seminar on the role of medical personnel in curing COVID-19 corpses through the provision of 4 topics by four presenters. The material provided was the ethical and legal aspects of the burial of COVID-19 bodies, the management of the burial of COVID-19 corpses, religious views on the handling of COVID-19 corpses, and filling out the COVID-19 death certificate. The results of the activities obtained are the pretest and post-test results to assess the participants' knowledge. Ninety-one participants attended the pretest, and 94 participants from 150 seminar participants attended the post-test. According to standard operating procedures adopted from WHO, the funeral of the corpse is carried out by taking into account ethical, cultural, and religious aspects. The province of West Sumatra itself is primarily Muslim, so this protocol is also based on the fatwa of the Indonesian Ulema Council. The preparation of SOPs for the healing of COVID-19 patients and socialization needs to be continued with other health workers and the community to reduce the turbidity in the community regarding the handling of the bodies of COVID-19 patients.